Studies on the treatment of anaerobically digested sludge by white-rot fungi: evaluation of the effect of Phanerochaete chrysosporium and Trametes versicolor - Xuefeng Zhu; Shicai Cheng; Zexian Fang; Guangyin Zhen; Xueqin Lu; Hongbo Liu; Jing Qi; Zhen Zhou; Xuedong Zhang; Zhichao Wu (Microbial Cell Factories)
Abstract Background The composition of anaerobically digested sludge is inherently complex, enriched with structurally complex organic compounds and nitrogenous constituents, which are refractory to biodegradation. These characteristics limit the subsequent rational utilization of resources from anaerobically digested sludge. White-rot fungi (WRF) have garnered significant research interest due to their exceptional capacity to degrade complex and recalcitrant organic pollutants. However, the exploration of WRF in the context of sludge treatment remains an under-investigated area within the scientific community. The present investigation explores the application of WRF in the treatment of anaerobically digested sludge, offering a novel approach for the valorization of sludge resources. Results In this study, WRF enzymes, manganese peroxidase (MnP) and lignin peroxidase (LiP), exhibited sustained high activities of approximately 102 U/L and 26 U/L, respectively, within the anaerobically digested sludge under a controlled pH of 5.5 within the growth system. These conditions were found to significantly enhance the treatment efficacy of the anaerobic sludge. The removal of soluble chemical oxygen demand (COD) and Total COD by Trametes versicolor powder was better than that of Phanerochaete chrysosporium powder. The treatment of sludge samples with WRF, specifically Phanerochaete chrysosporium powder, resulted in a significant reduction of ultraviolet radiation (UV254). Fourier-transform infrared spectroscopy (FTIR) analysis revealed that the application of Trametes versicolor powder exerted a notably pronounced impact on the functional groups present in sludge samples. Specifically, there was a significant decrease in the peak intensities corresponding to the C-O bonds, indicative of saccharide degradation, alongside an observable increase in the intensities of amide peaks, which is suggestive of protein synthesis enhancement. Microbial community analysis demonstrated that Phanerochaete chrysosporium was the predominant fungal species, exerting a significant regulatory role within the sludge ecosystem. Conclusion In conclusion, this research furnishes a robust scientific foundation for the utilization of WRF in the treatment of anaerobic digestion sludge. It elucidates the fungi’s capacity to ameliorate the physicochemical attributes and microbial community composition within the sludge. Furthermore, the study offers a certain reference for the subsequent use of WRF in the treatment of other types of sludge.